2017
DOI: 10.1111/evo.13251
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of divergence and introgression for speciation in Andean cloud forest birds

Abstract: Divergence with gene flow is well documented and reveals the influence of ecological adaptation on speciation. Yet, it remains intuitive that gene exchange inhibits speciation in many scenarios, particularly among ecologically similar populations. The influence of gene flow on the divergence of populations facing similar selection pressures has received less empirical attention than scenarios where differentiation is coupled with local environmental adaptation. I used a paired study design to test the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 112 publications
(275 reference statements)
0
28
0
Order By: Relevance
“…For example, some previous analyses have assessed factors influencing general introgression patterns with different approaches. For example, Winger () evaluated the relationship between introgression and plumage differentiation for 16 lineages of Andean cloud forest birds within a geographically and ecologically structured study. He found evidence for introgression across a geographic barrier between lineage pairs with uniform plumage patterns, but not between pairs with divergent plumage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some previous analyses have assessed factors influencing general introgression patterns with different approaches. For example, Winger () evaluated the relationship between introgression and plumage differentiation for 16 lineages of Andean cloud forest birds within a geographically and ecologically structured study. He found evidence for introgression across a geographic barrier between lineage pairs with uniform plumage patterns, but not between pairs with divergent plumage.…”
Section: Discussionmentioning
confidence: 99%
“…the acquisition of novel distributions) in the Neotropics, specifically with regard to Amazonian lineage emigration? In general, Neotropical diversification is widely attributed to allopatric isolation across biogeographic barriers [5 -9], even though these barriers are often species-specific [1] and spatio-temporally semi-permeable [6,10,11]. Dispersal across biogeographic barriers is often considered to be a stochastic process [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, minor allele frequency (MAF) thresholds directly influence the SFS by imposing a cutoff on the minimum allele frequency allowed to incorporate a specific genetic variant. However, despite its potential importance, the two most popular comprehensive bioinformatic pipelines for RADseq data alternatively include (Catchen, Hohenlohe, Bassham, Amores, & Cresko, 2013) or exclude (Eaton, 2014) the option to set MAF thresholds during variant calling, with the result that among empirical studies MAF thresholds are only sometimes reported (e.g., Winger, 2017, Blanco-Bercial & Bucklin, 2016.…”
mentioning
confidence: 99%